A personal perspective of an ESP teacher's professional development / Hawa Rohany - Rohany, Hawa (Academy of Language Studies & UPENA, 2005)
An ESP teachers' professional development is discussed as a personal process of learning, which can start at any time in one's career. It involves the rethinking, refocusing and re-strategising of one's teaching approaches and materials that must take into account the communicative language needs and skills of new jobs and emerging workplaces. The learning process recommended is not new to ESP but requires the teachers to renegotiate collaborative teaching principles that will ensure a position of synchronous partnership between the ESP teacher and content specialist. It also purports that some period of immersion in the specialist workplace would foster both confidence and competency in the discursive practices of the specialist profession.